2014
DOI: 10.3748/wjg.v20.i16.4662
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of glutamine on intestinal injury and bacterial community in rats exposed to hypobaric hypoxia environment

Abstract: Gln treatment protects from intestinal injury and regulates the gut flora imbalance in hypoxia environment. These effects may be related to the TLR4/MyD88/NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 35 publications
5
36
1
Order By: Relevance
“…This result suggests a reduction in oxidative stress in response to glutamine supplementation. Similarly, numerous well-designed investigations have consistently indicated that glutamine increases anti-oxidative capacity in mice (Ren et al 2014b;Cruzat et al 2014), rats (Xu et al 2014), pigs (Wu et al 2011b(Wu et al , 2013cWang et al 2008), and sheep (Sawant et al 2014;Washburn et al 2013). Furthermore, we found that dietary supplementation with 0.5 % glutamine decreased the expression of virulence factors of P. multocida, as we previously reported (Ren et al 2013e).…”
Section: Discussionsupporting
confidence: 80%
“…This result suggests a reduction in oxidative stress in response to glutamine supplementation. Similarly, numerous well-designed investigations have consistently indicated that glutamine increases anti-oxidative capacity in mice (Ren et al 2014b;Cruzat et al 2014), rats (Xu et al 2014), pigs (Wu et al 2011b(Wu et al , 2013cWang et al 2008), and sheep (Sawant et al 2014;Washburn et al 2013). Furthermore, we found that dietary supplementation with 0.5 % glutamine decreased the expression of virulence factors of P. multocida, as we previously reported (Ren et al 2013e).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we investigated the role and mechanism of resveratrol in lipid metabolism in rats when exposed to high altitude hypoxia environment for 30 days. Marked body weight loss was observed after high altitude hypoxia exposure, which was consistent with previous studies [3,21,22]. Moreover, less food intake was observed in our current and previous experiments.…”
Section: Discussionsupporting
confidence: 93%
“…Glutamate and L‐glutamine are the precursors of GSH, which is an important antioxidant that inhibits inflammatory reactions and reduces liver injury. Xu et al reported that enhanced L‐glutamine has a protective effect on rats with NAFLD induced by a high‐fat diet. Our previous studies on the metabolites of cirrhosis patients also revealed higher levels of glutamate and L‐glutamine in human serum …”
Section: Discussionmentioning
confidence: 99%